Bycatch of Amboina Box Turtle (Cuora amboinensis) by Fishermen in Rawa Aopa, Southeast Sulawesi - Harnum Nurazizah; Mirza Dikari Kusrini; Ani Mardiastuti (Universitas Gadjah Mada, 2022)
Rawa Aopa is a permanent swamp ecosystem that serves as one of the suitable habitats for amboina box turtles (Cuora amboinensis). Some of the area is part of a national park (Rawa Aopa Watumohai National Park) and is designated as a traditional zone for fishing activities, where local fishermen sometimes reported accidental catch C. amboinensis in their fishing gear. The aims of this study were to record the existence of C. amboinensis bycatch, size and age structure of bycatch, characteristic of fishing activity, and to discuss the conservation implication of bycatch. The number of bycatch was recorded by direct observation of 7 selected fishermen in 14 days. The C. amboinensis caught accidentally were measured and weighed. A total of 38 individuals of C. amboinensis were accidentally caught by fishermen during the study, having a size ranged of 7.4 to 18.5 cm (juveniles, young adults, and old adults; no hatchling), and weighed 248 to 996 g. Based on sex, there was no significant difference between morphological size of male and female, although bycatch for females (59%) tend to be slightly higher than males (41%). Most of fishermen lives in Pewutaa Village and used bubu traps to catch fishes. C. amboinensis are the most common bycatch compared to other species. In order to minimize the impact of bycatch of the C. amboinensis by fishermen, we need to ensure that the turtle that accidentally trapped in the fishermen’s fishing gear would be released unharmedly to their habitat.